Analysis of the sucrose synthase gene family in Arabidopsis. - Bieniawska, Z; Paul Barratt, D; Garlick, A; Thole, V; Kruger, N; Martin, C; Zrenner, R; Smith, A (2007)
The properties and expression patterns of the six isoforms of sucrose synthase in Arabidopsis are described, and their functions are explored through analysis of T-DNA insertion mutants. The isoforms have generally similar kinetic properties. Although there is variation in sensitivity to substrate inhibition by fructose this is unlikely to be of major physiological significance. No two isoforms have the same spatial and temporal expression patterns. Some are highly expressed in specific locations, whereas others are more generally expressed. More than one isoform is expressed in all organs examined. Mutant plants lacking individual isoforms have no obvious growth phenotypes, and are not significantly different from wild-type plants in starch, sugar and cellulose content, seed weight or seed composition under the growth conditions employed. Double mutants lacking the pairs of similar isoforms sus2 and sus3, and sus5 and sus6, are also not significantly different in these respects from wild-type plants. These results are surprising in the light of the marked phenotypes observed when individual isoforms are eliminated in crop plants including pea, maize, potato and cotton. A sus1/sus4 double mutant grows normally in well-aerated conditions, but shows marked growth retardation and accumulation of sugars when roots are subjected to hypoxia. The sucrose synthase activity in roots of this mutant is 3% or less of wild-type activity. Thus under well-aerated conditions sucrose mobilization in the root can proceed almost entirely via invertases without obvious detriment to the plant, but under hypoxia there is a specific requirement for sucrose synthase activity.